Linguiça frescal elaborada com carne de avestruz (struthio camelus) - Melo, Anne Emmanuelle Câmara da Silva (Universidade Federal Rural do Semi-Árido, 2018)
In Brazil, the market for ostrich meat has been increasing and encouraging the producers, directing their creations for sale of animals for slaughter. Fresh sausages with ostrich meat are a viable alternative of production and commercialization, being able to compete in the market with the traditional sausages with perspective of success. In this sense, the objective was to elaborate an ostrich meat with low fat content and to evaluate its microbiological, physical-chemical and sensorial quality. For this, ostrich meat shank was used in the manufacture of the product, which was milled on a 8 mm disc and weighed in the respective proportions for addition of each additive. A dry salting was performed and after homogenization the mass was allowed to stand for 12 hours under refrigeration to obtain the cure. After this period, it was embedded in pork casings, duly conditioned and stored under refrigeration. The raw material and the sausage were submitted to microbiological analyzes (coliforms at 350 and 450 C and absence of Salmonella spp.). In addition, the meat and the final product were submitted to physical-chemical analysis (pH, color, water retention capacity, shear force, cooking loss, moisture, ash, lipids and protein) and sensory (global acceptance test and attitude test). The ostrich meat was within the parameters recommended by the current legislation for the research of coliforms at 450 C and absence of Salmonella spp., As well as to the standards required in the physico-chemical aspect recommended by the Brazilian legislation. Regarding the overall acceptance test, 41% of respondents liked it very much. As for the intent-to-buy test, most testers replied that they would "buy often." Thus ostrich meat sausage presented a good acceptance by the consumer, being a viable option of production and commercialization, since the manufacture of this type of meat product does not need noble cuts
Keywords: Embutidos cárneos; Processamento; Carne exótica; Meat sausages; Processing; Exotic meat; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL